2017
DOI: 10.1159/000453523
|View full text |Cite
|
Sign up to set email alerts
|

Is Fat Mass Accretion of Late Preterm Infants Associated with Insulin Resistance?

Abstract: Background: Late preterm infants show a major fat mass accretion from birth to term. The contribution of preterm birth to the development of the metabolic syndrome is still under investigation. Objectives: To evaluate body composition changes in late preterm infants during the first 3 months and to investigate their insulin sensitivity and resistance. Methods: We conducted an observational, longitudinal study. A total of 216 late preterm infants underwent body composition assessment using an air displacement p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…Previous studies demonstrated obviously less weight and length growth in late preterm infants during first weeks of life than our study. The mean ΔLengthZ and ΔWeightZ of late preterm AGA infants from birth to term-corrected age in Nadia Liotto’s study [28] was − 0.27 and − 0.15, corresponding to our 0.28 and 0.66; The mean ΔLengthZ and ΔWeightZ of late preterm SGA infants in the same study [28] was 0.12 and 0.39, corresponding to our 0.30 and 0.75. The Preterm Postnatal Follow-up Study(PPFS) of the INTERGROWTH-21(st) Project [21] and a latest Chinese preterm cohort [29] both demonstrated slightly less weight increments.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies demonstrated obviously less weight and length growth in late preterm infants during first weeks of life than our study. The mean ΔLengthZ and ΔWeightZ of late preterm AGA infants from birth to term-corrected age in Nadia Liotto’s study [28] was − 0.27 and − 0.15, corresponding to our 0.28 and 0.66; The mean ΔLengthZ and ΔWeightZ of late preterm SGA infants in the same study [28] was 0.12 and 0.39, corresponding to our 0.30 and 0.75. The Preterm Postnatal Follow-up Study(PPFS) of the INTERGROWTH-21(st) Project [21] and a latest Chinese preterm cohort [29] both demonstrated slightly less weight increments.…”
Section: Discussionsupporting
confidence: 58%
“…The second possible reason was the differences in feeding and nutrition strategies. In Nadia Liotto’s study, none of the late preterm infants got fortified nutrients, including SGA [28]; while in our study, 5.2%(17 SGA and 14 AGA infants) belonged to MNR and got partially fortified nutrients before discharge (before they got 2000 g target weight), the vast majority(97.4%) of AGA and all LGA infants belonged to LNR and were fed on demand as full-term born infants. Whether this difference in nutrition strategies before discharge contributed to the obvious different growth results was needed for further exploration.…”
Section: Discussioncontrasting
confidence: 55%
“…In a first set of data on a limited number of patients (n = 49), the LPT infants had a similar fat content at 3 months corrected age than term infants ages 3 months, despite a transient higher percentage of fat at term corrected age and at 1 month corrected age (41). This transient increase in adiposity, which may simply come from the comparison of a newborn infant with one who is several weeks old, was confirmed by a second set of data of 216 LPT infants (42). Among the factors studied, intrauterine growth was not significantly associated with postnatal body composition changes, but more human milk feeding appeared to be associated with increased fat‐free mass deposition (43,44).…”
Section: Introductionmentioning
confidence: 66%
“…It remains uncertain whether the transient altered body composition observed in LMPT infants at term persists into later life, and if so, whether this may be mediated by early nutrition. Up until 3 months of age, fat mass accretion of LPT infants is not associated with early perturbation of glucose homeostasis (42). A population‐based study from Sweden showed that children born LMPT are significantly leaner at 5 years than those born at term (51).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatologists and pediatricians wish a progressive and adequate growth within the same percentile; however, it is usual for premature patients to suffer growth restrictions and accelerations, as a consequence of some pathology associated with their prematurity or due to their condition as premature babies. Thus, it has been described those premature patients, once reaching their full-term age, present an increase in fat mass and fat mass index, but not in lean mass, compared to controls born at term [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%